2019
DOI: 10.1155/2019/9056845
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic Acid C against Acetaminophen-Induced Acute Liver Injury by Attenuating Inflammation, Oxidative Stress, and Apoptosis through Inhibition of the Keap1/Nrf2/HO-1 Signaling

Abstract: Acetaminophen (APAP) overdose is one of the most common causes of drug-induced acute liver failure in humans. To investigate the hepatoprotective effect of salvianolic acid C (SAC) on APAP-induced hepatic damage, SAC was administered by daily intraperitoneal (i.p.) injection for 6 days before the APAP administration in mice. SAC prevented the elevation of serum biochemical parameters and lipid profile including aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin (T-Bil), total cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 37 publications
(52 reference statements)
3
93
0
Order By: Relevance
“…Cytokine Assay. Serum TNF-α, IL-1β, and IL-6 were evaluated with an ELISA kit (BioLegend, San Diego, CA, USA), according to the manufacturer's instructions [23].…”
Section: Nitritementioning
confidence: 99%
“…Cytokine Assay. Serum TNF-α, IL-1β, and IL-6 were evaluated with an ELISA kit (BioLegend, San Diego, CA, USA), according to the manufacturer's instructions [23].…”
Section: Nitritementioning
confidence: 99%
“…The liver damaged by oxidative stress is also activated by reactive oxygen species which provoke inflammatory cytokines such as IL-1β and IL-6 which further worsens liver damage [ 14 ]. Oxidative stress and inflammation are well documented to have the foremost protagonist in APAP facilitated liver damage [ 15 , 16 ]. In a study, reported by Das et al [ 17 ] confirms that APAP impairs mitochondrial membrane potential Δψm which encourage the discharges of cytochrome c that promote caspase-3 and -9 activation ended by hepatic cell death [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 attenuates CCl 4 -induced liver injury in mice and may be related to their antioxidant properties. Furthermore, the antioxidant enzymes including SOD and GSH-Px are mainly regulated by the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway, which is an important regulator of the antioxidant defense system [36,37]. However, more studies are needed to reveal whether Nrf2 pathway played a key role in liver protective activities of the AEMA and Comp.…”
Section: Discussionmentioning
confidence: 99%